The ventilation parameters during the Nuss procedure for repair of pectus excavatum - I.I. Myhal (Danylo Halytsky Lviv National Medical University, 2020)
The ventilation parameters during the Nuss procedure for repair of pectus excavatum depend on surgical procedures and airway protection technique.